Endothelial CCR2 signaling induced by colon carcinoma cells enables extravasation via the JAK2-Stat5 and p38MAPK pathway. - Wolf, Monika Julia; Hoos, Alexandra; Bauer, Judith; Boettcher, Steffen; Knust, Markus; Weber, Achim; Simonavicius, Nicole; Schneider, Christoph; Lang, Matthias; Stürzl, Michael; Croner, Roland S.; Konrad, Andreas; et al. (Cancer Cell, 2012)
Increased expression of the chemokine CCL2 in tumor cells correlates with enhanced metastasis, poor prognosis, and recruitment of CCR2(+)Ly6C(hi) monocytes. However, the mechanisms driving tumor cell extravasation through the endothelium remain elusive. Here, we describe CCL2 upregulation in metastatic UICC stage IV colon carcinomas and demonstrate that tumor cell-derived CCL2 activates the CCR2(+) endothelium to increase vascular permeability in vivo. CCR2 deficiency prevents colon carcinoma extravasation and metastasis. Of note, CCR2 expression on radio-resistant cells or endothelial CCR2 expression restores extravasation and metastasis in Ccr2(-/-) mice. Reduction of CCR2 expression on myeloid cells decreases but does not prevent metastasis. CCL2-induced vascular permeability and metastasis is dependent on JAK2-Stat5 and p38MAPK signaling. Our study identifies potential targets for treating CCL2-dependent metastasis.